Assessment of Renewable Electricity Consumption Determinants and its Implications in Malaysia - Azilah Hasnisah, A.A. Azlina (International Journal of Advanced Science and Technology, 2020)
This study is the first empirical attempt to investigate the determinants of renewable electricity consumption in Malaysia during the period from 1980 until 2014. For this purpose, Johansen cointegration and Vector Error Correction Model approach are applied. The empirical findings reveal that GDP per capita and trade openness encourage renewable electricity consumption. On the other hand, CO2 emissions, electricity consumption from fossil fuels and oil prices have negative implications on renewable electricity consumption. The result also reports the unidirectional causality running from renewable electricity consumption, GDP per capita, trade openness, electricity consumption from fossil fuels and oil prices to CO2 emissions in the longrun. In this regard, a comprehensive review of policies on renewable energy should be emphasised by the Malaysian government to increase energy from renewable sources not only to regulate pollution but also to generate the country’s economy.